Approach to Management of Thrombotic Thrombocytopenic Purpura at University of Cincinnati - N. Abdel Karim; S. Haider; C. Siegrist; N. Ahmad; A. Zarzour; J. Ying; Z. Yasin; R. Sacher (Advances in Hematology)
Thrombotic Thrombocytopenic Purpura (TTP) is a rare hematologic emergency, congenital or acquired, characterized by ischemic damage of various organs because of platelet aggregation. It is the common name for adults with microangiopathic hemolytic anemia, thrombocytopenia, with or without neurologic or renal abnormalities, and without another etiology; children without renal failure are also described as TTP. Plasma exchange (PE) is the main stay of treatment in combination with steroids and immunosuppressive therapies. The monoclonal antibody against CD20 Rituximab decreases the production of antibodies from B lymphocytes and it is used for antibodies-mediated diseases including TTP. We present our data on retrospective analysis of rituximab in treatment of TTP at University of Cincinnati in a series of 22 patients from 1997 to 2009. Our results showed that PE with immunosuppressive therapy resulted in decreased duration of PE, relapse rate, and increased duration of remission in patients with TTP.